Questioning immersion in digital literacies in the COVID-19 pandemic - Silva, Francisco Gabriel Cordeiro da; Costa, Marco Antônio Margarido (The ESPecialist, 2024)
This paper aims at analyzing and discussing the digital literacy practices of interns during the mandatory supervised internship from September to December 2020 of the Modern English Language course at a public university located in Northeastern Brazil. Due to the COVID-19 pandemic, the subject matter English Language Internship: 3rd year of High School took place completely remotely, through digital technologies. For the theoretical-methodological focus of this study, we selected some data and focused especially on the trainees’ understanding of the notion of immersion in digital literacies during the stages of the internship. By analyzing the data, it was possible to verify that, given the fact that most of the trainees stated that there was no immersion in digital literacies in this period, the apprehension of the literacy practices carried out is consistent with an autonomous perspective, referring to the notion of development of skills, in this case, with digital devices and resources, opposing the sociocultural and ideological perspective (Buzato, 2006; Kleiman, 1995; Lankshear, Knobel, 2011; Street, 1986, 2010, 2012).